Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1016/j.thromres.2022.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal multiparametric characterization of platelet dysfunction in COVID-19: Effects of disease severity, anticoagulation therapy and inflammatory status

Abstract: Introduction Defects of platelet functional responses in COVID-19 were reported, but their origin and pathophysiological significance are unclear. The objective of this study was to characterize the thrombocytopathy in COVID-19. Materials and methods Analysis of platelet functional responses to activation by flow cytometry and aggregometry in 46 patients with confirmed COVID-19 of different severity (non-ICU, ICU, and ECMO) over the course of hospitalization alongside w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 61 publications
0
21
0
1
Order By: Relevance
“…However, in recent studies, platelets from COVID-19 patients were shown to exhibit impaired aggregation and impaired activation of the responsible integrin receptor αIIbβ3 (GPIIb-IIIa) upon agonist-induced stimulation in vitro [ 56 , 57 ]. The reduced responsiveness of platelet functions ex vivo was not due to prior platelet activation in vivo.…”
Section: Pathogenesis Of Post-covid Syndromementioning
confidence: 99%
“…However, in recent studies, platelets from COVID-19 patients were shown to exhibit impaired aggregation and impaired activation of the responsible integrin receptor αIIbβ3 (GPIIb-IIIa) upon agonist-induced stimulation in vitro [ 56 , 57 ]. The reduced responsiveness of platelet functions ex vivo was not due to prior platelet activation in vivo.…”
Section: Pathogenesis Of Post-covid Syndromementioning
confidence: 99%
“…Platelet–leukocyte complexes were elevated in COVID-19 patients, with even higher numbers observed in ICU patients [ 155 ]. Platelets were pre-activated: changes in P-selectin exposure and GPIb shedding and elevated sizes and higher levels of sCD40L and sP-selectin were shown [ 156 , 157 , 158 ]. A recent review of COVID-19-associated thrombosis, focusing on all potential contributors, including platelets and neutrophils, was published [ 159 ].…”
Section: Platelets and Neutrophils Interactions In Homeostasis And Pa...mentioning
confidence: 99%
“…CD61 expression in the quiescent state ( supplemental Figure 3 C) was normal for all patients. Patients with KHE/KMP without HR had increased CD62p binding in the resting state, but these differences were not statistically significant ( supplemental Figure 3 D).In combination with the increased amounts of PS-positive platelets ( supplemental Figure 3 E), these results could be interpreted so that platelets are preactivated, 48 probably because of their contact with the tumor and consumption by it, and this resulted in decreased platelet counts and platelet age. 49 …”
Section: Resultsmentioning
confidence: 97%